P‐165: Using 1Domain Pixel Design to Improve the Transmittance Rate of UV2A. Issue 1 (May 2017) - Zhang, Yu; Song, Yan-Jun; Li, Xiang; Fan, De-Yong; Zhao, Yong-Chao; Zhao, Ren-Tang; Hsieh, Chung-Ching; Chiu, Chung-Yi; Lee, Chia-Yu
Abstract : 1Domain pixel design UV2A has been proposed by changing the way of exposure and it has high transmittance rate performance due to the disappearance of the dark lines in pixel. In order to compare the optical performance of 1Domain/4Domain, we prepared the 32HD 1Domain/4Domain panel. We have investigated the transmittance rate, visual angle and reliability of 1Domain/4Domain, to prove that 1Domain pixel is practicability in TV panel. Although the 32HD image quality is not very good due to the grid line, it is proved that the high resolution panel can effectively avoid the generation of the grid. And finally, a method to improve the quality of 1Domain TV is proposed.